The effects of suitability and acceptability of lean principles in the flow of waste management on construction project performance - Muhammad Faiz, Rosli; Abdul Rahman, Zahari; Puteri Fadzline, Muhamad Tamyez (Taylor & Francis, 2020)
Poor project performance in Malaysian construction industry resulting from poor cost management, time overrun, and inadequate quality has encouraged scholars to investigate the feasibility, suitability, and acceptability of lean principles in the construction sector. The purpose of this study was to assess the appropriateness and acceptability of lean principles by construction companies based in Pahang, Malaysia. This study applied quantitative methods and a simple random sampling technique to select 104 respondents from construction companies located in Pahang, Malaysia. The data were analyzed using partial least squares structural equation modelling (PLS-SEM). Results show that three variables in lean principles, namely operation in the flow of waste management, employee involvement in the flow of waste management, and continuous flow of waste management, support construction project performance. Conversely, information about flow in waste management negatively influences project performance. The findings from this study can be used as a guideline for better performance in cost management for Malaysia's construction industry.